2022
DOI: 10.1177/03611981221089545
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Urban Mode Choice Behavior During the COVID-19 Pandemic in Switzerland Using Mixed Multiple Discrete-Continuous Extreme Value Models

Abstract: This paper describes and models the behavioral response to the COVID-19 pandemic in Switzerland. The MOBIS-COVID GPS tracking dataset, which includes a pre-pandemic reference base, is used. Trip-level data are transformed in weekly distance proportions per mode per week, and the data are modeled using a mixed multiple discrete-continuous extreme value (MMDCEV) model. Four distinct segments are derived, from September 2019 until the end of 2020, and used to uncover natural and forced behavioral adaptations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…The pandemic should not be read as a structural break in mode preferences as only a few parameters were found to differ between the two observation periods. This is in stark contrast to the study by Molloy et al ( 4) and Meister et al (5) who found considerable modal shifts induced by the pandemic. The findings from this work suggest that these changes were not made habitual but can be attributed to the unprecedented circumstances and constraints brought by the pandemic.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The pandemic should not be read as a structural break in mode preferences as only a few parameters were found to differ between the two observation periods. This is in stark contrast to the study by Molloy et al ( 4) and Meister et al (5) who found considerable modal shifts induced by the pandemic. The findings from this work suggest that these changes were not made habitual but can be attributed to the unprecedented circumstances and constraints brought by the pandemic.…”
Section: Resultscontrasting
confidence: 99%
“…A very similar picture is portrayed in Figure 4 where we show average stage lengths and the average number of stages per day and by mode. The bicycle boom described by various authors (e.g., Molloy et al [4] or Meister et al [5]) has its foundation in the peak visible in the year 2020 and in bicycle being the only mode that benefited from restrictive measures. Despite bicycle stage lengths not reaching these very high levels, it is still the case that bicycle usage is slightly higher than during the pandemic.…”
Section: Descriptive Analysis Of Mobility Patternsmentioning
confidence: 99%
“…Cycling is becoming an increasingly popular mode of transport in many regions of the world. For Switzerland, and similar to other countries, the COVID-19 pandemic has boosted cycling activity (1) on top of a general trend of increased bike usage (2). Apart from their positive effects on health and low road space requirements, private (e)-bikes have very low life-cycle emissions and hence make them ideal to quickly decarbonize a substantial share of urban transport (3).…”
Section: Introductionmentioning
confidence: 99%
“…While many studies focused on mode choice behavior changes related to the pandemic, other studies investigated travel characteristics, such as travel distance. In Switzerland, compared to 2019, the travel distance of all means of transportation decreased by 50% at the beginning of the outbreak, and when the first restriction was implemented, the travel distance of public transportation decreased by more than 90% (Hintermann et al 2023;Marra et al 2022;Meister et al 2022). Using a survey distributed in various countries, found that the percentage of respondents who traveled for a short trip (a distance less than 10 km) dropped from 71% before the pandemic to 45% during the pandemic.…”
Section: Changes In Personal Travel Behavior Based On Surveysmentioning
confidence: 99%